Investigating risk factors for migraine in Syrian women: a cross-sectional case-control study - Nafiza Martini; Tamam Hawa; Mohamad Moamen Almouallem; Majd Hanna; Imad-Addin Almasri; Ghassan Hamzeh (Scientific Reports)
Abstract This study aimed to investigate the relationship between potential risk factors and migraine among Syrian women through a cross-sectional case-control design. A total of 989 women were enrolled, including 519 migraine patients and 470 non-migraine controls. Data collection involved a comprehensive questionnaire covering demographic information, clinical features, and medical history. Statistical analysis was performed using descriptive statistics and Chi-Square tests. The findings revealed that migraineurs were more likely to smoke, have a higher BMI, have a family history of migraines (particularly in first-degree relatives), have a surgical history, and have undergone a cesarean delivery. No significant associations were found between migraine and allergies, anemia, contraceptive use, or menstrual cycle regularity. These results support existing literature on smoking, BMI, and family history as established risk factors for migraine, while also highlighting the novel associations between migraine and surgical history and delivery type. The study emphasizes the importance of addressing modifiable lifestyle factors and understanding familial predispositions in managing migraine in Syrian women. Further research in this region is crucial for a better understanding of the disease and effective management strategies.